Critical review of a meta-analysis for the effect of single and multiple sets of resistance training on strength gains - Carpinelli, R. N. (Medicina Sportiva, 2012)
A meta-analysis is a controversial statistical procedure that combines the data from several independent studies in an attempt to produce an estimate for the effectiveness of a specific intervention. The validity of a meta-analysis, also known by its critics as numerological abracadabra, is dependent on the arbitrarily defined criteria and discrimination of the analyst, and more importantly, on the quality of the inclusive studies. The focus of this commentary is a meta-analysis by Krieger, who claimed that multiple sets of each exercise are superior to a single set of each exercise for increasing muscular strength. Some examples of the inclusive studies that he awarded the highest quality scores are shown in this Critical Review to be very poor quality studies and not acceptable for inclusion in a meta-analysis.